BIBLIOMETRIC ANALYSIS OF THE INCIDENCE OF NON-COVID RESPIRATORY DISEASE UNDER NPI CONDITIONS DURING THE PANDEMIC - Nji T. NDEH; Yacob T. TESFALDET; Oluseye OLUDOYE (Journal of Applied Life Sciences and Environment)
Publications associated with the incidence of respiratory diseases in light of the COVID-19 pandemic have skyrocketed. Using bibliometric analysis, this study assessed the characteristics of published articles regarding non-pharmaceutical interventions (NPIs) on other respiratory infections during the COVID-19 pandemic. On July 06, 2023, a systematic review of literature on the incidence of respiratory diseases was conducted using the Scopus database. VOS viewer software was used to visualize the network. This study yielded a total of 910 articles, which were eventually narrowed down to 148 articles. The findings of the bibliometric analysis revealed a trend in research that included not only the investigation of the incidence of other respiratory diseases but also that of gastrointestinal infections during the COVID-19 pandemic. Most of the research output was created by American and Chinese authors. Kim J. H. was the most productive and cited researcher, with three research articles. There is a scarcity of data on the effectiveness of NPI in preventing the spread of other respiratory diseases among various age groups, including children, adults, and vulnerable populations. Countries should consider increasing their support for COVID-19 research, to generate knowledge pertaining to NPIs and, by extension, other infectious diseases with similar transmission mechanisms.